On the nonlinear influence of Reserve Bank of Australia interventions on exchange rates - Stefan Reitz; Jan C. Ruelke; Mark P. Taylor (Deutsche Bundesbank, 2010)
This paper applies nonlinear econometric models to empirically investigate the effectiveness of the Reserve Bank of Australia (RBA) exchange rate policy. First, results from a STARTZ model are provided revealing nonlinear mean reversion of the Australian dollar exchange rate in the sense that mean reversion increases with the degree of exchange rate misalignment. Second, a STR-GARCH model suggests that RBA interventions account for this result by strengthening foreign exchange traders' confidence in fundamental analysis. This in line with the so-called coordination channel of intervention effectiveness.
Keywords: C10; F31; F41; 330; Foreign exchange intervention; market microstructure; smooth transition; nonlinear mean reversion; Wechselkurspolitik; Wirkungsanalyse; Wechselkurs; US-Dollar; Devisenmarkt; Mikrostrukturanalyse; Nichtlineares Verfahren; Schätzung; Australien